Prospects of Nanostructure Materials and Their Composites as Antimicrobial Agents - Baranwal, Anupriya; Srivastava, Ananya; Kumar, Pradeep; Bajpai, Vivek K.; Maurya, Pawan K.; Chandra, Pranjal (Frontiers in Microbiology, 2018)
Nanostructured materials (NSMs) have increasingly been used as a substitute for antibiotics and additives in various products to impart microbicidal effect. In particular, use of silver nanoparticles (AgNPs) has garnered huge researchers’ attention as potent bactericidal agent due to the inherent antimicrobial property of the silver metal. Moreover, other nanomaterials (carbon nanotubes, fullerenes, graphene, chitosan, etc.) have also been studied for their antimicrobial effects in order ensure their application in widespread domains. The present review exclusively emphasizes on materials that possess antimicrobial activity in nanoscale range and describes their various modes of antimicrobial action. It also entails broad classification of NSMs along with their application in various fields. For instance, use of AgNPs in consumer products, gold nanoparticles (AuNPs) in drug delivery. Likewise, use of zinc oxide nanoparticles (ZnO-NPs) and titanium dioxide nanoparticles (TiO2-NPs) as additives in consumer merchandises and nanoscale chitosan (NCH) in medical products and wastewater treatment. Furthermore, this review briefly discusses the current scenario of antimicrobial nanostructured materials (aNSMs), limitations of current research and their future prospects. To put various perceptive insights on the recent advancements of such antimicrobials, an extended table is incorporated, which describes effect of NSMs of different dimensions on test microorganisms along with their potential widespread applications.